Teaching Foreign Students-Philologists Russian National-Specific Phraseological Units - Misenyova, V. V. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The given article is devoted to the research of the nationally-oriented principle in training the Russian phraseology in multinational students’ audience. In phraseological units national identity of the language receives the brightest and direct manifestation as they are correlated directly with extralanguage reality. Revealing of national and cultural specifics of the phraseological units’ semantics of one language can be carried out only in comparison with the phraseological unit of the student’s native language, and allocation of common features of two languages promotes fast understanding of national and cultural component’s semantics. Comparison of phraseological units gets a special practical sense in the linguocultural aspect which promotes not only the expansion of the students’ background and the formation of their linguocultural competence, but also allows to warn the specific mistakes caused by the interference and to eliminate the influence of the students’ native language and culture. Relying on the observations of the linguists and methodologists of Russian as a foreign language in our country and on the author’s experience of teaching foreign students-philologists as well, the main differences of Russian and Eastern phraseological systems have been considered in the article; the difficulties of learning national-specific phraseological units have been described and systematized. The main attention is focused on the expedient use of the comparison of the student’s native language and the target one to establish the similarity and distinction of the compared units as well as the degree of this similarity or distinction. It serves as a basis for structuring the content of training in which the nationally-oriented approach of teaching a foreign language in the definite national audience is carried out. According to the author’s findings the consideration and accounting of the problems, which are solved in thе article, allow to increase the efficiency and quality of training national-specific phraseological units of the Russian language to foreign students-philologists.